PENDIDIKAN PEMILIH PEMILU: STRATEGI PENGUATAN PENGAWASAN PARTSIPATIF MASYARAKAT - Moh Sitoh Anang (Universitas Islam Depok, 2022)
In other words, the notion of political participation is the participation of the community in making political decisions in the context of elections, meaning that the community is given space in making decisions because the community can make their choices, the certainty of using voting rights is given access to be able to monitor all stages and processes, and obtain complete information. and true about who the candidates for representatives are. The most important thing is access and active involvement in election supervision, so that the public can control the votes they cast in the ballot box, this can be started from updating the voter registration, so that it is designated as a voter list, access to vote without pressure, being given space to supervise voting and counting of votes to the process of vote recapitulation, to the determination of election results, as well as broad access when suspected violations are found, the community can report it to the election supervisor, and this can be called participatory election supervision where the community consciously takes part in determining the direction of the nation's democracy. through elections.